Generation difference in hiring financial planners in Malaysia - Mansori, Shaheen (Emerald Publishing Limited, 2017)
Purpose The purpose of this paper is to document a gap between generation X and Y’s behavior toward decision making for hiring a professional financial planner in context of an emerging country.